DAMPAK NEGATIF PROYEK PEMBANGUNAN RUMAH TINGGAL TERHADAP BANGUNAN DI SEKITARNYA – STUDI KASUS DI SURABAYA - Daniel Tjandra; Paravita Sri Wulandari (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
The need for housing in a metropolitan city such as Surabaya will increase with time. These needs can be met by building new houses or renovating. Sometimes the construction and renovation of houses will more or less have an environmental impact on the surrounding buildings. The case study in this paper aims to increase public awareness of the impact of construction project on the surrounding buildings. The case study was conducted by doing field observations on the location of a residential house construction which had an impact on the adjacent houses, located on the right and left side. It was obtained that the damage to the adjacent houses was caused by the demolition of the old building, the addition of loads, and the process of compaction of the backfill. Repair and strengthening of buildings must be carried out to restore the function of the building and prevent further damage. Unfortunately, repairing the building requires significant additional costs and causes the construction time to be longer.